Effect of Pretreatments of Seed for Enhancing Germination of Vitex Altissima L. - Sudhakara, K.; Veenadevi, K. R. (Indian Forester, 2013)
Vitex altissima L., a threatened tree species with high conservation value in the Western Ghats of India, has low germination rates, hindering the restoration of this species. In addition to studying the drupe characteristics of V. altissima, various pre-treatments were conducted to enhance the seed germination rates. The treatments included alternate wetting and drying, soaking in GA3 solution and fire. The number of days for initiation and completion ofÂ germination varied from 10 to 16 and 74 to 93 respectively. Overnight soaking of the drupes in 300 ppm GA3 solution increased the germination percent,mean daily germination, peak value and germination value by 280 per cent,260 per cent, 311 per cent and 1416 per cent compared to the control. This was closely followed by GA3 solution 200 ppm soak overnight and 300 ppm soak for 30 min., alternate wetting and drying of drupes for ten days and straw fire treatment.